Automated Management of Time Extension Claims in Construction Projects - elazhary, mariam (AUC Knowledge Fountain, 2024)
Disputes within the construction industry have caused parties to incur additional costs not accounted for. In fact, one of the notorious reasons for disputes can be attributed to Extension of Time (EOT) claim submissions. Such is due to its susceptibility to the human factor. Accordingly, there is a need to diminish reliance on the human factor in the EOT process and to bolster it with commodities of the industrial revolution 4.0. While research efforts have endeavored in tackling the drawbacks of the EOT claim process individually, no superior solution is provided to overcome all drawbacks at once. Initially, the literature was analyzed by utilizing a citation-based mapping tool to pinpoint the prominent features affecting the success of the EOT claim process. Then, disadvantages of the features were analyzed within the literature as follows: poor record keeping, delayed event notification, an arduous process of EOT-related clauses within contracts, the lack of a superior delay analysis technique (DAT), no automation of a DAT, lack of standardized EOT submission reports, and finally mistrust/security issues between parties This research strives to overcome the disadvantages present within the EOT submission process caused by the human factor by creating a web-based EOT management system model utilizing a distributed platform shared between all parties to decentralize and proactively deal with EOT claim management. The model, Automated Management of Time Extension Claims (AMTEC), was created using ASP.NET: a cross-platform for web development powered by Microsoft. The language used to develop AMTEC is C# (C-Sharp). Features of AMTEC are tailored to overcome the EOT seven drawbacks through: live delay information updates and approvals inclusive of relevant documentation; natural language programming to extract EOT-related clauses; a superior DAT that was created to overcome existing DATs drawbacks’; the automation of the DAT through the model that not only obliterates the manual aspect but also the need to deal with a complicated project management software; and finally a standardized reporting system that generates a claim tailored to the needs of the engineer for the ease of the claim review process. This research also explores a framework for future implementation of the model through blockchain technology to facilitate interactions between parties within the delay analysis implementation process and create a secure, auditable network to increase the level of trust between the parties. AMTEC was then applied to a case study involving an EOT claim submission; it was initially applied manually and then using AMTEC. The level of effort, duration, and disputes within the entire process were compared in both scenarios. Results show that the duration for the processes decreased by 79% and the level of effort was decreased by 52%. Disputes within both scenarios were further analyzed and it was established that AMTEC was capable of overcoming the disputes faced within the manual process between parties. Thus, creating the foremost application of a claim management system, involving all parties, that is carefully designed to allow an efficient and less disputed EOT submission.